Doctors Without Borders: The Returns to an Occupational License for Soviet Immigrant Physicians in Israel - Adriana D. Kugler; Robert M. Sauer (Institute for the Study of Labor (IZA), 2002)
Re-licensing requirements for professionals that move across borders are widespread. In this paper, we measure the returns to an occupational license using novel data on Soviet trained physicians that immigrated to Israel. An immigrant re-training assignment rule used by the Israel Ministry of Health provides an exogenous source of variation in re-licensing outcomes. Instrumental variables and quantile treatment effects estimates of the returns to an occupational license indicate excess wages due to occupational entry restrictions and negative selection into licensing status. We develop a model of optimal license acquisition which suggests that the wages of high-skilled immigrant physicians in the nonphysician sector outweigh the lower direct costs that these immigrants face in acquiring a medical license. Licensing thus leads to lower average quality of service. However, the positive earnings effect of entry restrictions far outweighs the lower practitioner quality earnings effect that licensing induces.
Keywords: J24; J17; D45; J61; J31; J62; L51; L15; 330; licensing; occupational mobility; regulation; information and product quality; immigration; Migranten; Ärzte; Arbeitsmarkt; Berufsrecht; Bildungsertrag; Israel; Sowjetunion